Między uczciwością a skutecznością działania politycznego. Fundamentalny dylemat wyborcy - Nocoń, Jarosław (Political Preferences, 2013)
The main thesis of the article assumes, that honesty and effectivenes or eficacy are complementary values of political action. This claim is still valid especially in conemporary normative political theory. Meanwhile, the results of empirical research shows, that voters perceive voters both of these features, as the contradictions of political action. The author analyzes the key reasons of this contradiction and indicates the conditions of its limitations.